CONFLICT SITUATIONS ON THE EXAMPLE OF PRESCHOOL EDUCATION - Otajonov Jamshid Mashrabjonovich; Ergasheva Zilolakhan Murodillaevna (Zeta Repository, 2023)
The article reveals the pedagogical conditions for managing conflict situations in the team of a preschool educational organization.